Management of High-Water-Cut and Mature Petroleum Reservoirs - Pål Østebø Andersen; Ketil Djurhuus; Reza Askarinezhad; Jonas S. Solbakken (Energies, 2022)
An increasing number of oil and gas companies reach their economic limit after years of production, exhausting the support of natural-pressure drive mechanisms in the reservoir and the benefits of water or gas injection [...]